Perceptions and Dispositions of Parents and Teachers Toward Technological Learning Communities - Núñez-Hernández, Corina (2023)
The search for strategies to improve students’ academic performance is increasingly common in education. Parents’ participation and teachers’ attention are key factors in forming a learning community. This article presents the results of a survey in which relevant statistical data was obtained. A significant association (p = 0.571) was found between the frequency with which parents help their children understand school content and their willingness to be part of a learning community, representing 40.65% of the population. In addition, it was found that 66.67% of parents frequently meet with their children’s teachers because they often solve the children’s doubts. Regarding the attention of teachers, it was evidenced that 64.71% of parents who meet very frequently with teachers do so with those who very frequently resolve children’s doubts effectively, which shows a correlation significant (p = 0.467). Finally, the relationship between the degree of mastery of teachers in learning management platforms and their participation in forming learning communities was analyzed. A significant correlation (phi = 0.321) was found between the degree of mastery of teachers in these platforms and their participation in the formation of learning communities, with 28.24% of teachers having sufficient mastery and 20.61% of those with a moderate domain. These findings highlight the importance of parent-teacher collaboration in fostering a culture of learning in school and improving student academic achievement.